METODE LATIHAN CIRCUIT TRAINING TERHADAP AKURASI MEMANAH PADA ATLET UKM PANAHAN PUTRA UNIVERSITAS NEGERI SEMARANG - Agung Hadi Saputro; Hermawan Hermawan; Rubianto Hadi; Arif Setiawan (Universitas Negeri Semarang, 2022)
The importance of physical exercise in archery is because archery is a sport that requires endurance of the arm muscles, shoulder muscles and abdominal muscles. Lack of physical exercise programs in the Student Activity Unit. This study aims to determine the effect of the Circuit Training method towards Accuracy in male Archery Students Activity Unit athletes at UNNES 2021.This research method is quantitative with an experimental approach and is included in the Pre Experimental design type. The instrument used is a test score of 30 meters distance. The research subjects were 10 athletes from the Archery UKM UNNES. Data analysis technique using t test.The results of the t test obtained are t arithmetic (2.003) > t table (1.739) with a significance value (sig) 2-tailed (0.03) < (0.05) then Ha is accepted and Ho is rejected which means that the circuit training has an effect on Archery UKM Athletes UNNES 2021 Archery Accuracy.Based on the results of the processed data, it can be concluded that there is a significant increase in the archery accuracy of the athletes of Male ArcheryStudents Activity Unit UNNES.